The Role of Digital Tourism Marketing: The Relationship Between Immersive Tourism and Metaverse on Bleisure Travelers at Malang Hotels - estikowati, estikowati; Kuntariati, Utik; Alvianna, Stella; Hidayatullah, Syarif (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2025)
This study explores the relationship between digital tourism marketing, immersive tourism, and the metaverse in the context of bleisure travelers visiting Batu Tourism City. By understanding how digital marketing can facilitate immersive tourism experiences, this study is expected to offer assistance to stakeholders in the tourism industry in designing more effective marketing strategies. The rapid development of technology and the increasing dependence of consumers on technology when selecting tourist destinations heighten this relevance. This research is an exploratory study that uses a quantitative approach to explore the relationship between several variables in the context of tourism. The two independent variables analyzed are immersive tourism and metaverse experience. In addition, there is one mediating variable, namely tourism digital marketing, and one dependent variable, namely bleisure. Results from the study showed that immersive tourism and metaverse experiences have a strong effect on digital tourism marketing, and that metaverse experiences directly improve bleisure behavior. Additionally, digital tourism marketing serves as a vital mediator between metaverse experiences and bleisure behavior. Therefore tourism in Batu needs to integrate digital technologies such as the metaverse and AR/VR to enhance global competitiveness and tourist attraction.